2017
DOI: 10.1002/ange.201701486
|View full text |Cite
|
Sign up to set email alerts
|

Das Distortion/Interaction‐Activation‐Strain‐Modell zur Analyse von Reaktionsgeschwindigkeiten

Abstract: Das Activation‐Strain‐ oder Distortion/Interaction‐Modell ist ein Instrument zur Analyse von Aktivierungsbarrieren und damit von Reaktionsgeschwindigkeiten. Für eine bimolekulare Reaktion ergibt sich die Aktivierungsenergie aus der Summe der Energien, die für die Deformation der Grundzustandsgeometrie der Reaktanten benötigt wird, um die Geometrie des Übergangszustands anzunehmen, plus der Wechselwirkungsenergie zwischen diesen deformierten Reaktanten. Die mit der Deformation assoziierte Energie wird “activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 215 publications
(22 citation statements)
references
References 137 publications
(74 reference statements)
0
21
0
1
Order By: Relevance
“…In order to gain a deeper understanding of the effect of the α-methyl substituent, we performed an activation strain (ASM) -distortion/interaction analysis [12] of the reaction profiles. The obtained activation strain diagrams (ASDs) are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to gain a deeper understanding of the effect of the α-methyl substituent, we performed an activation strain (ASM) -distortion/interaction analysis [12] of the reaction profiles. The obtained activation strain diagrams (ASDs) are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…The computed reaction profiles were analyzed using the activation strain (ASM) -distortion/interaction model [12] developed by Bickelhaupt -Houk, respectively, modified to include solvation effects. [31] Within this framework, the solution-phase energy profile ΔE solution (ζ) is decomposed along the reaction coordinate ζ into the energy of the solute ΔE solute (ζ), the reaction system in vacuum but with its geometry in solution, plus the solvation energy ΔE solvation (ζ) [Eq.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…To gain additional insight, we analyzed the energetic profiles of these nine reactions using the activation strain model. [35] Initially,w es peculated that the bulky tert-butyl groups in R 1 could diminish the planarity of the benzene ring, lowering the distortion energy and making it easier to break aromaticity.However,the calculation results showed that the presence of the bulky substituents in R 1 causes energetically favorable dispersive interactions at longer C À Cd istances, whereas no major difference in strain energy was observed (Figure 1). This results in an earlier, lower energy transition state for the tert-butyl containing variant relative to methyl or hydrogen.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…As shown in Figure 5, the energy of optimized transition state TS-9 is 2.7 kcal mol À1 lower than that of TS-11 (si-face attack to give ent-6a), in good agree- To better elucidate the origin of observed enantioselectivity,w ep erformed ad istortion/interaction analysis of the transition states. [37] Thes tructures of TS-9 and TS-11 are divided into three fragments:c atalyst (R)-A,b enzaldehyde, and the allylboronate ( Figure 5). Thec alculated distortion energy of TS-11 is 2.1 kcal mol À1 lower than that of TS-9, while the interaction energy of TS-11 is 4.6 kcal mol À1 higher than that of TS-9.T herefore,t he overall energy of TS-11 is 2.5 kcal mol À1 higher than TS-9 based on the distortion/ interaction analysis model, indicating transition state TS-9 is more favorable than TS-11.…”
Section: Angewandte Chemiementioning
confidence: 99%